Purification and characterization of thermostable alpha-galactosidase from Ganoderma lucidum - Sripuan T. (2014)
Alpha-galactosidase was purified from a fresh fruiting body of Ganoderma lucidum by precipitation with ammonium sulfate and column chromatographies with DEAE-Sephadex and Con A-Sepharose. The purified enzyme was homogeneous on polyacrylamide gel electrophoresis. Its N-terminal amino acid sequence was similar to that of Mortierella vinacea alpha-galactosidase. The molecular mass of the enzyme was about 56 kDa by SDS-polyacrylamide gel electrophoresis, and about 249 kDa by gel filtration column chromatography. The optimum pH and temperature were 6.0 and 70 degrees C, respectively. The enzyme was fully stable to heating at 70 degrees C for 30 min. It hydrolyzed p-nitrophenyl-alpha-D-galactopyranoside (Km=0.4 mM) but hydrolyzed little o-nitrophenyl-alpha-D-galactopyranoside. It also hydrolyzed melibiose, raffinose, and stachyose. The enzyme catalyzed the transgalactosylation reaction which synthesized melibiose. The product was confirmed by various analyses.